HUBUNGAN SPIRITUAL LEADERSHIP DENGAN KINERJA PERAWAT DALAM MELAKSANAKAN ASUHAN KEPERAWATAN - Silvia Dewi Mayasari Riu; Faradilla Miftah Suranata (Universitas Muhamadiyah Manado, 2021)
Introduction. Leadership is a very decisive factor in the success of an organization. Spiritual leadership that is applied at the hospital are believed to be capable of evoking motivation of nurses can further improve the implementation of nursing care. The purpose of this research is to know the relationship of Spiritual Leadership With the nurse Performance in performing Nursing Care. Research methods. done using penilitian Type used is Descriptive Analytic with Crossectional draft. The sample numbered 36 respondents using Simple Random Sampling techniques. Data collection is done by distributing questionnaires and observation sheets. Furthermore the data that has been collected is processed using computer-assisted program SPSS version 16.0 for analysis by using the chi square statistic test with significance level (α) 0.05. The results. in this study, there is a Spiritual Relationship With the nurse Performance Leadership In Implementing Nursing Care. Obtained p = the value of 0,018 showed < α = 0.05. The discussion. The results of this study expect can add information that can be used to improve the performance of the nurses in the care of nursing.